Narcolepsy in children and young people in Ireland: 2006–2017. (September 2020) - Gill, Irwin; Sheils, Aishling; Reade, Elaine; O'Malley, Siobhan; Carey, Aoife; Muldoon, Maeve; Wagle, Abigail; Crowe, Catherine; Lynch, Bryan
Abstract: Aim: To describe the population of young people in Ireland diagnosed with narcolepsy with regards to vaccine exposure, symptomatology, investigation results and experience of medical treatment. Method: Retrospective review of medical records at the single tertiary referral centre for young people with narcolepsy in Ireland. Results: Sixty-seven patients were diagnosed with narcolepsy between July 2006 and July 2017. Sixty-one (91%) of these developed symptoms after receiving the Pandemrix vaccine. The population was largely homogeneous with low hypocretin (87.5%), HLA DQB1∗0602 positivity (95%) and unremarkable findings on MRI Brain (100%). 77.6% experienced cataplexy; we also measured high levels of obesity, school non-attendance and psychosocial complexity. Symptoms often continued despite treatment, with multiple medications prescribed in 76.1% of patients. Prescription of sodium oxybate was associated with a significant reduction in BMI standard deviation scores at 6 months, with improved IOTF obesity scores seen at 36 month follow-up. Conclusions: This paper describes the experience of narcolepsy in children and young people in Ireland from 2006 – 2017 at the national tertiary referral centre. Narcolepsy in children and young people in Ireland carries a significant burden of illness, with impact on participation in education as well as physical and mental health. Symptoms can be refractory to medical treatment. Referral to tertiary centres for prompt treatment and multidisciplinary input is essential. Highlights: This study describes the Irish national experience of narcolepsy in children and young people since 2009. The population was largely homogeneous with low hypocretin, HLA DQBQ∗0602 positivity, and normal MRI Brain. Pandemrix vaccine exposure preceded symptom onset in the majority of cases. Symptoms of narcolepsy were resistant to treatment with single agents; medication side-effects were common. High levels of obesity, school non-attendance and psychosocial complexity are described.